2016
DOI: 10.1177/1524839916651400
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effectiveness of the Smoking Prevention Program “I Do Not Smoke, I Exercise” in Elementary and Secondary School Settings

Abstract: The aim of the study was to examine the effectiveness of the smoking prevention program "I do not smoke, I exercise" implemented with elementary and secondary school students. "I do not smoke, I exercise" is a theory-based smoking prevention program that promotes exercise as an alternative of smoking. The program consists of eight sessions implemented weekly. Participants were 338 Greek students (135 elementary and 203 secondary students) who were pre- and posttested in smoking, program, and exercise-related m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
4
8
0
Order By: Relevance
“…This finding suggests a target age for smoking prevention programs; they would be most effective if implemented before the majority of adolescents start smoking (Hwang & Park, 2014;Park, 2009). Kolovelonis, Goudas, and Theodorakis (2016) reported that smoking prevention programs in elementary school settings had more positive effects to change elementary students' attitudes toward smoking, intention to smoke, subjective norms, and attitudes toward the application of the program in comparison to secondary students' attitude. Therefore, such programs should be provided to both sex groups by at least late in elementary school (Hwang & Park, 2014;Park, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…This finding suggests a target age for smoking prevention programs; they would be most effective if implemented before the majority of adolescents start smoking (Hwang & Park, 2014;Park, 2009). Kolovelonis, Goudas, and Theodorakis (2016) reported that smoking prevention programs in elementary school settings had more positive effects to change elementary students' attitudes toward smoking, intention to smoke, subjective norms, and attitudes toward the application of the program in comparison to secondary students' attitude. Therefore, such programs should be provided to both sex groups by at least late in elementary school (Hwang & Park, 2014;Park, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies have effectively used the TPB to predict the link between smoking behavior and TPB's variables [26,27]. Moreover, it has been effectively used to design, implement, and evaluate theory-based, behaviorchange antismoking interventions [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Lareyre et al [30], after conducting a systematic review of TPB-based interventions for smoking behavior, found that the percentage of studies reporting a significant impact on smoking behavior, intention, attitude, subjective norm, or perceived behavioral control ranged from 42% to 50%. For example, results of studies applying health education behavior change interventions utilizing the TPB, intending to prevent smoking among adolescents, indicate significant effects on the TPB constructs post-intervention [29,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other similar educational approach, the program BI do not smoke, I exercise^-a theory-based smoking prevention program that promotes exercise as an alternative of smoking-yielded positive effects on adolescents' awareness for lung cancer prevention in Greek secondary schools [28]. The authors highlighted the importance of integrating physical activity into smoking prevention strategies, especially to improve students' attitudes towards smoking and awareness about the health consequences of smoking [28].…”
Section: Awareness Of Warning Signs and Risk Factors For Lungmentioning
confidence: 99%
“…Our findings align with those found in a similar single-group, pretest/posttest program evaluation of a teacher-led version of the St. Jude Cancer Education for Children Program (SJCECP) in fourth-grade students from 10 local schools in Memphis area [27]. Moreover, other similar educational approach, the program BI do not smoke, I exercise^-a theory-based smoking prevention program that promotes exercise as an alternative of smoking-yielded positive effects on adolescents' awareness for lung cancer prevention in Greek secondary schools [28]. The authors highlighted the importance of integrating physical activity into smoking prevention strategies, especially to improve students' attitudes towards smoking and awareness about the health consequences of smoking [28].…”
Section: Awareness Of Warning Signs and Risk Factors For Lungmentioning
confidence: 99%